The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1975
DOI: 10.1021/ac60363a004
|View full text |Cite
|
Sign up to set email alerts
|

Alternating current polarographic evidence for the reversible reduction of trivalent gallium from acidified 1.0 M sodium thiocyanate at 60.deg.

Abstract: Clinical research (1-5) has established that neoplastic sarcomas and certain categories of carcinoma (lung, breast, colon, etc.) (6) exhibit a pronounced tendency to sequester serum gallium citrate and other gallium salts. The metal's therapeutic effectiveness in regressing or arresting malignant growth-either as absorbed nonradiogallium ( 6 ) or as (principally) the 67 isotope used for in situ radiotherapy (2)-has prompted exploration of new benchtop analytical procedures ( 7 ) for the measurement of trace Ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
10
0

Year Published

1976
1976
1992
1992

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…The results of PSAS peak current vs. bulk Ga(lll) concentration, peak current reproducibility for 67.8 ppb Ga(lll), and standard addition experiments are tabulated, with the first two compared to accompanying differential pulse anodic stripping (DPAS) measurements on the same solutions. While our 1.0 M NH4SCN PSAS results at 60 °C indicated that Ga can be measured rapidly with fair precision down to 20 ppb, it is necessary to conclude from a comparative evaluation of the influences of , , , and pH for the room temperature vs. high temperature cases that the 60 °C procedure is experimentally somewhat less flexible and, at the present time, probably more suitable to specialized applications.Electroanalytical and electrochemical studies of the catalyzed reversible gallium electrode reaction (GER) have achieved the stage (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) where rapid and inexpensive anodic stripping methods [e.g., phase-selective anodic stripping (PSAS), or differential pulse anodic stripping (DPAS)] can be applied under special conditions for the analysis of samples containing trivalent gallium in the 1 to 10 parts-per-billion (ppb, or ng/g) range. Potentially useful areas for clinical application of these methods for rapid tissue…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…The results of PSAS peak current vs. bulk Ga(lll) concentration, peak current reproducibility for 67.8 ppb Ga(lll), and standard addition experiments are tabulated, with the first two compared to accompanying differential pulse anodic stripping (DPAS) measurements on the same solutions. While our 1.0 M NH4SCN PSAS results at 60 °C indicated that Ga can be measured rapidly with fair precision down to 20 ppb, it is necessary to conclude from a comparative evaluation of the influences of , , , and pH for the room temperature vs. high temperature cases that the 60 °C procedure is experimentally somewhat less flexible and, at the present time, probably more suitable to specialized applications.Electroanalytical and electrochemical studies of the catalyzed reversible gallium electrode reaction (GER) have achieved the stage (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) where rapid and inexpensive anodic stripping methods [e.g., phase-selective anodic stripping (PSAS), or differential pulse anodic stripping (DPAS)] can be applied under special conditions for the analysis of samples containing trivalent gallium in the 1 to 10 parts-per-billion (ppb, or ng/g) range. Potentially useful areas for clinical application of these methods for rapid tissue…”
mentioning
confidence: 99%
“…Electroanalytical and electrochemical studies of the catalyzed reversible gallium electrode reaction (GER) have achieved the stage (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) where rapid and inexpensive anodic stripping methods [e.g., phase-selective anodic stripping (PSAS), or differential pulse anodic stripping (DPAS)] can be applied under special conditions for the analysis of samples containing trivalent gallium in the 1 to 10 parts-per-billion (ppb, or ng/g) range. Potentially useful areas for clinical application of these methods for rapid tissue…”
mentioning
confidence: 99%
See 3 more Smart Citations